Management of Small Bowel Perforation by a Bizarre Foreign Body in a 55-Year-Old Woman. (12th September 2018) - D'Auria, Francesca; Consalvo, Vincenzo; Canero, Antonio; Russo, Maria; Rescigno, Carmela; Lombardi, Domenico
Abstract : Introduction . Ingestion of foreign bodies including dentures, fishbone, screw, and/or surgical devices can be a cause of morbidity, and it rarely could be fatal. Presentation of Case . We present the first hitherto reported case of mussel shell ingestion, which caused acute abdominal pain in a 55-year-old woman. The shell pierced ileal loops, and it was found in the abdominal cavity. Discussion . The accidental or voluntary ingestion of a foreign body is an uncommon event compared to the other causes of bowel perforation. It is fundamental to immediately remove the intestinal fluid, repair the tear, and prevent sepsis, because each delay in diagnosis can lead to a worst outcome. Conclusion . In case of bowel perforation, it important for surgeons, who are dealing with these acute care patients, to be aware of different designs and constructions of possible foreign bodies, in order to be prepared to deal with different possible scenarios and be able to manage them properly.